Manajemen Pemasaran dalam Peningkatan Penerimaan Peserta Didik Baru di SDN 1 Model Selebung Ketangga - Hamdi, Miftahul (ARZUSIN, 2023)
Management Marketing is the process for increase efficiency and effectiveness from activity Marketing done by individuals or by school. Management Education marketing is related systems between producers and consumers in something organization for fulfil learning with well, p This characteristic subjective Because There is each other need and each other Study together. Competition in the world of education is inevitable. In order to be able to maintain its existence, schools are required to be able to market their schools, because no matter how good a school is, if it is not promoted optimally, it will have an impact on the minimum number of students and not be recognized by the community. The purpose of this research is to know and describe How management, implementation and evaluation Management Marketing in enhancement reception participant educate implemented at SDN 1 Model Selebung Neighbors . The type of research method used is a descriptive qualitative research method to examine in depth and focus on increasing student acceptance through Marketing Management and studied in depth with a view to understanding the conditions and atmosphere at SDN 1 Selebung Ketanga Model with how Marketing Management is carried out so that it can attract students' interest. What was made data source is head school, vice principal school, teachers and guardians of students as subject data source. As for procedure deep data collection study This is interview, observation and documentation. Data analysis technique used in study qualitative covers data reduction, data display, and conclusion or verification. step for technique data validity is technique ie with technique triangulation and member check ie with request agreement informant. The results of the research show that : marketing management at SDN 1 Selebung Ketangga model is the process of preparing marketing plans carried out by school leaders, this is because the plans implemented can be arranged more effectively, the implementation of marketing management in increasing student acceptance in this case is a form the realization of the program that has been announced in the promotion process plan using the media of brochures, pamphlets, through student guardians, through friends and the most superior is through the community itself and Evaluation of Marketing Management in Increasing New Student Acceptance.